Macroeconomic modelling of CBDC: A critical review - Ulrich Bindseil; Richard Senner (European Central Bank (ECB), 2024)
Over the last decades, macro-economists have renewed their efforts to reduce the gap between monetary macroeconomics and real-world central banking. This paper reviews how macroeconomics has since 2016 approached the possible introduction of retail central bank digital currencies (CBDC). A review of the literature reveals that macroeconomic models of CBDC often rely on CBDC design features and narratives which are no longer in line with the one of central banks actually working on CBDC. In particular, the literature often (i) does not take into account the nature of central banks' CBDC issuance plans as a "conservative" reaction to profound technological and preferential shifts in the use of money as a means of payments, (ii) does not start from design features communicated by central banks, such as no-remuneration, quantity limits, access restrictions, and automated sweeping functionality linking CBDC wallets with commercial bank accounts; (iii) does not explain well enough the difference between CBDC and banknotes within their macro-economic models, apart from remuneration (which central banks actually do not foresee); and (iv) assume that CBDC will lead to a significant increase in the total holdings of central bank money in the economy, although (i) and (ii) make this unlikely.
Keywords: E3; E5; G1; 330; central bank digital currencies; macroeconomics; financial stability; central bank money